Ciudad rica y ciudadanos pobres. La consideración de la riqueza en el republicanismo florentino - Castillo Vegas, Jesús Luis (Ingenium. Revista Internacional de Pensamiento Moderno y Metodología en Historia de las Ideas, 2014)
Reading the classics, studying history and careful observation of the political practice of time will lead to Machiavelli to break with the humanist tradition on the property and to defend the need for limitations on it. The republican conception of the land is owned by the motto of the city’s rich and poor citizens. This is a policy of moderation which excludes alike oligarchic conception of those who confuse the wealth of the city with their rulers, and radical egalitarianism with its exclusiveness denying the existence of the two humors (umori) that make properly coordinated a republic with a mixed government, safe, stable and rich.